Nursing Care of Chronic Kidney Disease with Activity Intolerance Nursing Problems: A Case Study - Leni Agustin; Mofidah; Hamidah Retno Wardani (Health and Technology Journal (HTechJ), 2023)
Nursing care for patients who experienced chronic kidney disease with intolerance of activities and nursing problems in the Bougenville Room at Dr.H.Koesnadi General Hospital, Bondowoso Regency. Chronic Kidney Disease (CKD) is an irreversible disease that develops slowly and progressively. The main factor causing this disease is adults with Diabetes Mellitus and Hypertension. Symptoms are pain, hematuria, anuria, and anemia. This of course results in a feeling of weakness and fatigue so that the problem of Activity Intolerance can arise. This study aims to carry out nursing care for clients who experience chronic kidney disease with activity intolerance nursing problems. The research design was a case study of one patient with chronic kidney disease with Activity Intolerance nursing problems in the internal care room (Bougenvile) Dr.H. Koesnadi Bondowoso. Data was collected on 15-16 May 2023 using interviews, observation, physical examination, documentation studies, and questionnaire techniques. The results of this study were obtained from the assessment, which then formulated a diagnosis in accordance with the theoretical review. Nursing interventions using SIKI adapted to the client's conditions, implementation, and evaluation referring to the results criteria obtained are 99% O2 saturation, RR 19 x/minute, decreased complaints of fatigue, and decreased feeling of weakness. Clients are expected to always maintain their health condition, especially fluid intake, and balanced nutrition to support kidney function and fulfill daily activities.